Topology Molecular Indices Relationship of Electronic Properties of N-Alkanes and Branched Alkanes - Alias, Ahmad Nazib; Zabidi, Zubainun Mohamed; Zakaria, Nurul Aimi; Mahmud, Zaidatul Salwa (Iraqi Journal of Science, 2023)
Eight electronic properties; HUMO, LUMO, HOMO-LUMO energy gap, dipole moment point-charge, dipole moment hybrid, molecular weight, heat of formation and zero-point energy of 60 normal and branched alkanes were examined using topology molecular indices. All the electronic properties were calculated using semi-empirical self-consistent molecular orbital theory. The relationship of electronic calculation properties with seven models of topology indices based on degree and/or distance were obtained in terms of their correlation, regression and principal component analysis. Most of the properties were well-modelled (r2 > 0.82) by topology molecular indices except the dipole moment point-charge and hybrid. The PCA resulted in 7 properties and 60 structures of alkanes that produced two principal components with eigenvalues of greater than 1. The first principal component explained 60.388%, while the second principal component explained 26.457%, bringing a cumulative value of 86.845% to the data variation.